KOMPETENSI JURU DAKWAH - Nawawi Nawawi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
dakwah obligation isn’t an easy task. A dai (preacher) have to have appropriate competence to attaindakwah’s goal. These competences are substantive competence and methodological competence. Substantivecompetence consists of knowledge, understanding, comprehension, and application of religious teaching. Methodologicalcompetence related with dakwah planning and methodology. If these two competence mastered by juru dakwah(preacher), his dakwah will be successful